Occupational Stress Among Primary School Teachers : A Study in Jilin Province - Wen, Xin; Talwar, Prashanth; Tan, Kok Wah; Nur Fatihah, Mat Yusoff; Oon, Yin Bee; Kartini, Abd Ghani (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of this study was to study the association between selected demographic characters and stress among primary school teachers. The respondents constituted of 60 male and female school teachers who were chosen using stratified sampling technique. Study was conducted in Jilin Province. Study design was cross sectional. SPSS was used to analyze both descriptive and inferential statistics. The main results were as follows. Female teachers experienced more stress compared to male teachers. Teachers below the age of 40 had more stress probably, due to teaching experience, as this study revealed that teachers who had more teaching experience had less stress. Marriage plays and important role in stress, unmarried teachers experienced comparatively higher levels of stress compared to those married. Furthermore, those living alone experienced more stress. Occupational stress is known to cause burnout. It may be a good strategy to provide training in stress management techniques